Analisis Perhitungan Persediaan Barang dengan Metode Perhitungan Fifo dalam Perspektif Keuangan Syariah : (Studi Kasus Toko Saro Niaga Watampone) - Sulfianti Sulfianti; Munawarah Munawarah; Rini Idayanti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This research aims to analyze inventory management using the First-In, First-Out (FIFO) method at the Saro Niaga Grocery Store in Watampone from a sharia financial perspective. The FIFO method was chosen because of its ability to maintain product freshness and support sharia principles, such as transparency, fairness and honesty. The research uses a descriptive qualitative approach with data collection techniques through interviews, observation and documentation. The research results show that implementing the FIFO method effectively helps minimize the risk of losses due to expired goods, increases operational efficiency, and maintains the quality of goods provided to consumers. From a sharia perspective, this method supports responsible management and meets Islamic business ethical standards. This research provides practical recommendations for other traditional grocery stores to improve operational efficiency and conformity with sharia principles.